Optimization of off-grid solar generating system with DC-DC converter - I Ketut Parti; Suratno; Ni Wayan Rasmini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Electrical energy is a very complex problem for every country in the world, as well as in Indonesia in particular, with the rapid progress of the country’s industry, of course, followed by an increase in the generation of electrical energy. While the current energy generation most often comes from fossil fuels, which are increasingly depleting, the energy supply will decrease and increase sales. Therefore, every country is competing to find other energy for electrical energy generation. Renewable energy is a green energy generator whose supply is abundant and inexhaustible. Solar power plants (PLTS) are one of the green energies developed by the Indonesian government to utilize energy derived from non-fossil fuels. To support this, it is necessary to study and research to be done using the DC-DC up/down converter is expected to obtain results that can be used as a reference in the development of solar power plants (PLTS). With a DC-DC up/down converter, the voltage stabilization produced by PLTS can be stabilized by a DC-DC converter from 9 volts DC to 11.5 volts for a minimum voltage. Above 12 volts to 18 volts, up to 12 volts can be stabilized.